SINERGI MASYARAKAT SIPIL DALAM MENGHADAPI PERGESERAN POLA GERAKAN TERORISME DI INDONESIA - Khamdan, Muh (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2024)
This article describes changes in the movement patterns of terrorist networks and anticipatory strategies carried out by the government through the synergy of civil society coalitions. The first act of terrorism that occurred since the Bali Bombing I in 2002, has experienced a transformation of the target objects and objectives of the struggle movement. The first generation of terror targeted actions as revenge against the government and citizens of the United States and coalition countries. The shift in the terror movement occurred after the birth of the Terrorism Law which made security forces the target of terror because they tended to be repressive and paid little attention to human rights in taking action. This paper uses a qualitative method that explains data using content analysis methods. The primary sources for this article are documents relating to the shifting patterns of terrorist movements in Indonesia as well as the synergistic activities of civil society in handling terrorism in Indonesia. An ethic of care that prioritizes empathy is the key to civil society synergy in reducing the potential for the development of violent extremism.